The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s43055-021-00492-3
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell nebulization therapy for COVID-19 infection: radiological and clinical outcomes

Abstract: Background SARS-CoV-2 is a highly contagious virus that spread worldwide with a rapid increase in the number of deaths. In March 2020, the WHO declared SARS-CoV-2 a pandemic. The primary diagnostic test is reverse transcription-polymerase chain reaction, but chest X-ray and computed tomography have become the typical diagnostic tools used to detect abnormal lung changes. Within the framework of the SENTAD COVID Study clinical trial, an observational and analytical study was conducted, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Inhaled bacteriophage aerosol has been considered as an alternative to inhaled antibiotics in pulmonary infections [ 128 ]. Some attempts have also been made in the field of inhalation of living cells [ 129 ], including the aerosol delivery of stem cells in COVID-19 treatment [ 130 ]. All these innovative concepts still require optimization of the aerosolization technique to ensure that sensitive biomolecules are not damaged due to the high stresses encountered during atomization.…”
Section: Selected Concepts and Methods Of Improvement Of Targeted Aer...mentioning
confidence: 99%
“…Inhaled bacteriophage aerosol has been considered as an alternative to inhaled antibiotics in pulmonary infections [ 128 ]. Some attempts have also been made in the field of inhalation of living cells [ 129 ], including the aerosol delivery of stem cells in COVID-19 treatment [ 130 ]. All these innovative concepts still require optimization of the aerosolization technique to ensure that sensitive biomolecules are not damaged due to the high stresses encountered during atomization.…”
Section: Selected Concepts and Methods Of Improvement Of Targeted Aer...mentioning
confidence: 99%
“…High resolution computed tomography of chest (HRCT) was done to detect radiological signs of COVID 19, which include: no abnormalities, ground glass opacity, consolidation patches, and fibrosis. Based on the CORAD-scoring the patients were classified into 5 categories [5] .…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…New treatment strategies, such as nanomedicine-based approach, cell-based therapy, and adoptive immunotherapy have emerged to treat COVID-19 patients [ 21 23 ]. Among these, cell-based therapies using mesenchymal stem cells (MSCs), have shown promising results in pilot studies and also in clinical trials [ 24 26 ]. Our previous study also observed positive effects of MSCs in severe COVID-19 cases [ 27 ].…”
Section: Introductionmentioning
confidence: 99%